Pengaruh KAP Big Four, Komite Audit Dan Kepemilikan Institusional Terhadap Audit Delay - Merdianto Budi Utomo; Aristha Purwanthari Sawitri (Majalah Ekonomi, 2021)
The purpose of this study is to determine the effect of KAP reputation, Institutional Ownership audit Committee on audit delay (studies on manufacturing companies listed on the IDX in 2015 - 2019), this research method uses quantitative, the sampling technique uses purposive sampling with certain criteria. The test used is the classical assumption test, multiple linear regression analysis, the coefficient of determination (R2) and partial t, the results in this study are the reputation of public accounting firms has a positive and significant effect on audit delay because the significance value is 0.036 <0.05. The audit committee has a positive and significant effect on audit delay because the significance value is 0.044 <0.05. Institutional ownership has no positive and significant effect on audit delay because the significance value is 0.220> 0.05,.